Speeded up testing of solid body according to intensity of infrared emission - Дмитриев, Н. Н.; Скрипец, А. В. (Proceedings of National Aviation University (archive), 1998)
Considered is undistinctive speeded up method of testing which allows to determine with high precision resistance limit of metal samples both under condition of delivery and after preliminary loading or under different technological operations